MASLAHAT DALAM PENETAPAN HUKUM QISHAS: STUDY TERHADAP TAFSIR AHKAM KARANGAN SYEKH MUHAMAD ALI SAYS QS. AL-MAIDAH: 45 - Ahmadi, Nurul; Pranata, Rendi (Jurnal Al-Dirayah, 2019)
Maslahat is the fundamental purpose of Islamic law. All that are Allah commanded by Allah through His lawcontain benefit dan kindness to anyone who done it and vice versa all that Allah prohibited contain vices. None of His law is meaningless. Allah has put human beings at the highest level of creation, honored them among His creations, and protects and look after mankind?s life. Qishas was created by Allah to prevent human beings from the vice of human act that endangerhis spirit and body.